KEBIJAKAN BELARUSIA MENJADIKAN MATA UANG KRIPTO SEBAGAI ALAT INVESTASI INTERNASIONAL - Encik Zikri Nurkholis Syamsi; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Belarus has the most comprehensive regulatory framework regarding digital currency, where the regulations is directly issued by President Alexander Lukashenko which contains detailed liberalization of digital money. Given the decentralized nature, anonymity, and complexity of digital money, governments in many countries are having trouble to regulate such technology. Various economic problems of Belarus, such as lack of resources, currency crisis, and continuous economic recession forced the country to take new economic stabilization measures, one of which is regulation of digital money. This writings explains Belarus’s strategy to increase foreign investment through digital money as payment instrument.There are several policies that Belarus has taken in this regard. Firstly to legislate digital money technology, secondly increasing protection for participants in modern financial technology, thirdly giving prioritization and privileges to participants in modern technology; and lastly build a dedicated platform for digital money exchange. Keywords: Belarus, digital money, international investment, policy